Pengembangan media pembelajaran berbasis Android dalam keterampilan membaca pada siswa kelas X SMA Fransiskus 2 Jakarta - Irene Ivon Afiani; Ratna; Andika, Yunilis (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2023)
This research aims to develop android-based learning media in French reading skills for class 10th grade in high school. The method used in this research is Research and Development (R&D), and used ADDIE model which consists of five stages, namely analysis, development, implementation, and evaluation, but in this study it is only limited to the third stage, namely the development stage. The learning media was developed based on reading skill material of 10th grade and produces an android application that can be access via smartphone. This media named “Languese” which consists of menu of objectives and KD, instructions for use, vidéo, leçon, quiz, profile and référence. This learning media has been validated by media and material experts by getting a score of 93.75% and in categorized very feasible criteria to be applied to learning with remark that it is suitable for trial after revision and can be used as an alternative learning media that can be acces anywhere and anytime for students